Aflatoxin in groundnuts at retail premises in the district of Gombak, Selangor / Aisyah Nur Che Mohd Rose - Che Mohd Rose, Aisyah Nur (Faculty of Health Sciences, 2015)
Mycotoxins are toxic secondary metabolites and most mycotoxins produced by filamentous fungi can grow on food, especially before harvest and in storage. When humans and animals eaten, inhaled or absorbed through the skin mycotoxins, it can cause illness or death to humans and animals. There are 20 groups of secondary metabolites of fungal aflatoxins but only four identified aflatoxin in foods that aflatoxin B1 (AFB1), Aflatoxin B2 (FB2), Aflatoxin G1 (AFG1) and Aflatoxin G2 (AFG2) (Polychronaki et al., 2008: Liu, Y., and Wu, F.2010) A COMPARATIVE